Linguistic Attitudes and Activities of Petras Klimas. Diplomat’s Written Language in Private Correspondence - Aidukaitė-Mikelionienė, Deimantė (Tautosakos darbai, 2025)
The epistolary legacy of diplomat Petras Klimas is valuable not only in terms of disclosing the geopolitical, social and cultural reality of the interwar Lithuania and Europe, but also as an important corpus of manuscripts enabling us to trace the development of the written language. Having evaluated the field of P. Klimas’ activities that is currently rather overlooked by the modern scholarly discourse, i. e. his endeavors to accumulate the resources of the living language, to enhance the prestige of the Lithuanian language, and to solve issues related to its development, the author of the article identified the typical features of his written language and compiled a collection of paremias. The study is based on a hitherto unanalyzed correspondence of P. Klimas and his wife Bronislava Klimienė.An analysis of his personal writings has brought to light orthographical variations and causes, as well as the national attitudes reflected in his modified spelling. P. Klimas, it turns out, often inserted paremia, various French words and even words of his own making following Lithuanian standard word-formation, into his speech. This has allowed him to shape a unique, distinctive prose style that merges traditional (ethnic) and modern (Western) elements.
Keywords: Petras Klimas; egodocument; written language; paremia